Social protection in old age through taxes? An empirical analysis of the equity impact of taxes on pensions in the EU - Ella-Marie Assal; Sakura Panagamuwa Gamage; Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2023)
Living standards in old age are affected both by the pension system and the tax system. Yet, little research analyses the interaction between both systems. In this paper, we connect the principles of the pension system (solidarity vs. insurance) to the principles of the tax system (vertical equity vs. horizontal equity), and analyse to what extent they are in line with each other for 28 European countries. We find that horizontal equity is not relatively more important in insurance-based countries, nor is vertical equity relatively more important in solidarity-based countries. Countries that deviate from horizontal equity are able to do so without taxing pensioners into poverty. In contrast, where the tax system deviates from horizontal equity in favour of workers, this comes at the cost of taxing relatively larger shares of pensioners into poverty. Our results highlight the interlinkages of both systems and the importance of studying them together.
Keywords: D04; D31; H22; I38; I32; 330; tax-benefit system; pension system; old age poverty; pension taxation; equity principles